Systematic manipulation of experimenters' non-verbal behaviors for the investigation of pain reports and placebo effects - Daniali, Hojjat; Ruben, Mollie A.; Flaten, Magne Arve (Frontiers in Psychology, 2023)
Objective: Nonverbal behaviors (NBs) of caregivers affect pain reports and placebo effects. However, little experimental research has systematically examined the caregivers' NBs. This study protocol and preparatory study reports a systematic manipulation of experimenters’ NBs to investigate on placebo effects. Methods: We propose an experiment in which videotaped experimenters (VEs) conduct a pain stimulation and a placebo study. The VEs express one positively enhanced NB and keep other NBs neutral. Participants will be randomized to either the positive facial expressions (+FE), tone of voice (+TV), body movement (+BM), or neutral NBs (i.e., neutral condition; NC) of the VEs. As a preparatory study for proof of concept, two groups of NB coders from Norway and USA separately rated the degree of NBs (eye contact, body postures and movements, tone of voice), and impressions of dominance and being in charge, positivity, and expressivity from each NB video. The NBs videos had construct validity and reliability. The +BM and +FE were rated as more dominant and in charge than +TV and the NC. The +FE and +BM were rated as the most positive and expressive NBs, respectively. Expected results: +FE will have the largest placebo effects on pain and stress levels. However, transmitting the NBs to patients by VEs is challenging. Moreover, controlling for the effects of research assistants present in the testing room is challenging. Discussion: We propose that caregivers’ NBs affect the placebo effects. Moreover, different NBs elicit different impressions, and a better understanding of the role of caregivers’ NBs requires more rigorous investigations. Lastly, aiming to investigate the caregivers’ NBs, the varying degrees of micro-NBs and their effects in formation of impressions should be considered.